40-12x=40-12x

Simple and best practice solution for 40-12x=40-12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 40-12x=40-12x equation:


Simplifying
40 + -12x = 40 + -12x

Add '-40' to each side of the equation.
40 + -40 + -12x = 40 + -40 + -12x

Combine like terms: 40 + -40 = 0
0 + -12x = 40 + -40 + -12x
-12x = 40 + -40 + -12x

Combine like terms: 40 + -40 = 0
-12x = 0 + -12x
-12x = -12x

Add '12x' to each side of the equation.
-12x + 12x = -12x + 12x

Combine like terms: -12x + 12x = 0
0 = -12x + 12x

Combine like terms: -12x + 12x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 4m-28=8 | | 10x-(2x-5)=69 | | 3*2x+5*3y+3*4x-4*4y+2*3y= | | -14+5=x+9 | | 7n*8= | | (3x+15)+(2x+25)= | | x^3=39 | | b/14-22=3 | | -31-4v=-7(5v-3) | | (-4-3)= | | -(x-3)=30 | | -m-7=-8+8m+m | | 4ln(4x+2)=22 | | 6(n+4)=2(2n+4) | | -4(3y-7)-y=-2(y-3) | | X-5.1=7.7 | | 40x^2=41x+21 | | -5h+8-9=34 | | 5x^2-10x/x-2 | | (7y+8)-(3x+6y)=12 | | 26x+2=5(5x+2) | | -4(1+6k)+2=-4(6k+5) | | 3x+1(-0.4+0.6)= | | 2/5x=3/7=1-4/7x | | 0.3k^2-0.6k=2.4 | | 9x-4x+8=x-7+15 | | 7.9+x=0.4 | | 5(1-2x)=13-6x | | 7+4y=29 | | f(x)=ln(4-x) | | -15=x+11 | | 68/25 |

Equations solver categories